Study of nectar scale characters in annual Ranunculus from Ranunculuceae in Iran - Nahid sadat Emady; Maneezheh Pakravan fard; Tayebeh Amini (تاکسونومی و بیوسیستماتیک, 2010)
Ranunculus L. is one of the largest genera in Ranunculaceae with 6oo species. Because of high variability and polymorphism among different individuals and populations of certain species, taxonomy of this genus has always been problematic. Previous research showed that characters of nectar scale was a suitable character in separate species. Main aim of present work was to revise these characters in annual species of Ranunculus. We studied herbalial specimens or fresh material. Different shapes of nectar were observed such as Horseshoe type in R. dolosus, R. sceleratus and in the other species, scale with different shapes. To find out the significant differences in the characters, we used Analysis of Variance (ANOVA test). This study showed that these characters possessed taxonomical value in annual Ranunculus.